A questão feminina no movimento das contradições da escola pública do Rio de Janeiro e/ou: quem é esta mulher que se torna professora? - Faria, Lia Ciomar Macedo de (1989)
The present dissertation tries to identify the ways the woman's problem affects the class of teachers, mostly a feminine profession, analysing, from this point, the obstacles to a real change in Public School. Within the movement of contradictions that effervesces our State School, the woman's problem arises as one of the determiners forovercoming ar not the conservatism that, even today,well characterizes this Brazilian Public School, since the Republican period. The history of womanls condition, through the centuries, denotes a continuous struggle for the right to participate in the public sphere, mainly by means of the worting processo This is a proof that woman's 'imprisonment', in private 1 ife, has nothing to do with biological characters, but it has to do with multiple political, social and economical determinations of every society, in a particular historical momento And this 'imprisonment' wil1 be one of the obstacles for the woman-teacher to become a conscious professional, critically contributing to the improvement of our School. In the last decades (from the 60s. on), it has been noticed a clear movement of rebel1ion that wil1 give place to feminine leaderships, struggling not only for woman's liberation, but also for deep changes in our School and in society as a whole. Today, the petrified presence of the WOMAN in Brazilian official history as: *'mucama' (home servant), *'sinhã-moça' (little miss), slave ar *'professorinha' (little teacher) is already announcing a possibility of change as to the building horizon of the NEW WOMAN, subject of her own history, a skilful professional and political activist. This NEW TEACHER will no longer be the *'tia' (auntie) or the 'professorinha' (little teacher), but will finally be a CITIZEN ... 'BECOMING A WOMAN' (Beauvoi r)